Thermoreversible behavior of associating polymer solutions: thermothinning versus thermothickening - Hourdet, Dominique; Gadgil, Jayant; Podhajecka, K.; Badiger, Manohar V.; Brulet, A.; Wadgaonkar, P. P. (Macromolecules, 2005)
Self-assembling properties of poly(sodium acrylate) grafted with dodecyl [C12], PAAgC12, or poly(N-isopropylacrylamide) [PNIPA] side chains, PAAgPNIPA, were studied in unentangled semidilute aqueous solution. While PAAgC12 self-associates through hydrophobic interactions, the gelation of PAAgPNIPA is triggered by heating in response to the lower critical solution temperature of PNIPA (LCST similar to 32 degrees C). The local structure of the physical networks was investigated by small-angle neutron scattering, and the scattering patterns were described using a polydisperse sphere model taking into account hard-sphere interactions. This model allow us to draw a realistic picture of physical gels with quantitative information concerning the size of hydrophobic cores, the volume fraction of stickers in the aggregates, the fraction of stickers which take part in the aggregation process, the range of repulsive interactions, and the structural modifications induced by temperature. The description of the network is in good agreement with complementary data obtained from DSC and C-13 NMR. In the present work, a special emphasis has been given to the important relationship existing between the viscoelastic properties of associating polymer solutions and the binding energy of stickers leaving temporarily the micellar junction. Depending on the endothermic or exothermic nature of the disengagement process of the sticker (heat of demicellization), the relaxation time of the network and the viscoelastic properties will either decrease or increase with the temperature. The consequence is that aqueous solutions of PAAgC12 and PAAgPNIPA exhibit opposite rheological properties with the temperature, namely thermothinning and thermothickening. By mixing these two copolymers, we show that intermediate properties can be obtained but in that case a microphase-separated network is obtained as a result of copolymer segregation.

Thermodynamic behavior of hydrophobically modified polyacrylamide containing random distribution of hydrophobes: experimental and theoretical investigations - Hourdet, Dominique; Ducouret, Guylaine; Varghese, Sony; Badiger, Manohar V.; Wadgaonkar, Prakash P. (Polymer, 2013)
Two series of Hydrophobically Modified Polyacrylamides (HMPAMs) were prepared by free radical copolymerization of trimethylsilylacrylamide with 3-pentadecylcyclohexylacrylamide (PDCAM) or dodecylacrylamide (DDAM) followed by removal of trimethylsilyl protecting groups. The solution properties of HMPAMs were studied in dilute aqueous solution by fluorescence spectroscopy, NMR and viscometry. The properties in aqueous solution of HMPAMs clearly displayed the formation of hydrophobic interactions between alkyl stickers. While dodecyl containing HMPAMs mainly showed a progressive collapse of the copolymer coil with the increasing fraction of hydrophobic moieties (weak intra-chain associations), pentadecylcyclohexyl groups containing HMPAMs exhibited a much lower solubility in water due to strong intra- and inter-chain associations. Experimental data were analyzed using the mean field theory developed by Semenov and Rubinstein (SR) for associating polymers. Using a set of realistic parameters, taking into account the solubility of the backbone, the fraction of stickers and the strength of hydrophobic attractions, we show that the SR model offers a quantitative description of the thermodynamic properties of HMPAMs in terms of individual and collective behavior of polymers chains; i.e. swelling and phase separation, respectively. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Polyacrylamide; Self-assembling

Toughening of epoxy novolac resin using cardanol based flexibilizers - Gour, Rajeshwari S.; Kodgire, Vivek V.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2016)
In this work, two different cardanol based epoxies (Cardolite NC-514 and Cardanol NC-547) were employed as flexibilizers to toughen an epoxy novolac resin namely, poly[(phenylglycidyl ether)-co-formaldehyde] (PPGEF). 4,4-Diamino-3,3-dimethyl dicyclohexyl methane (BMCHA) was used as a curing agent. Differential scanning calorimetry and dynamic mechanical thermal analysis of the composites showed a gradual decrease in glass transition temperatures (T-g) with increase in cardolite content confirming the incorporation of flexible moieties into the brittle resin matrix. Improvement in toughening of PPGEF/Cardolite composites was manifested by increase in the izod impact strength of both the composites. The tensile strength increased marginally for composites with increasing amount of Cardolite NC-514 but decreased for the composites containing Cardolite NC-547. This was attributed to the lack of rotational motion in the chain due to close proximity of rigid phenyl rings in NC-547. SEM of the cryo-fractured surfaces of composites showed good compatibility between PPGEF and cardanol based flexibilizers. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43318.
Keywords: composites; crosslinking; glass transition

Thermo-reversible sol-gel transition of aqueous solutions of patchy polymers - Parmar, Indravadan A.; Shedge, Aarti S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Lele, Ashish K. (RSC Advances, 2017)
While aqueous solutions of several amphiphilic thermo-reversible polymers show gelation upon heating, there are fewer examples of polymer solutions that exhibit gelation when cooled. This paper reports an interesting phenomenon of abrupt thermoreversible gelation of aqueous solutions of a hydrophobically modified polymer upon cooling. A high molecular weight precursor copolymer (PCP, (M-w) over bar approximate to 5 x 10(6) g mol(-1)) of N, N-dimethylacrylamide (70 mol%) and acrylic acid (30 mol%) was modified by reacting 10 mol% of the acrylic acid groups with n-dodecyl amine to form a hydrophobically modified copolymer (HMCP). The composition of the copolymer was ascertained using NMR spectroscopy. Cooling the solution of PCP at a controlled rate resulted in a gradual increase in its low shear viscosity as dictated by the flow activation energy. In contrast, cooling the solution of HMCP under identical conditions resulted in an abrupt and large non-Arrhenius increase in viscosity at a specific transition temperature, which decreased with decrease in polymer concentration. Fluorescence measurements and dynamic light scattering data showed that abrupt gelation happened upon cooling, when polymer coils percolate accompanied with concomitant transition in chain conformation from compact micellar coils formed by intra-chain hydrophobic associations to swollen polymer coils connected by inter-chain hydrophobic interactions.

Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation